(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The impetus for this research work arose from alleged signs of Lead (Pb) poisoning from Medicines Sans Frontiers (Doctors without Borders).These poisonings were narrowed down to areas of solid minerals mining and extraction in Northern Nigeria. The aim of this research work is to identify mining Sites with ores having high Pb concentration. Fifteen samples were collected from areas located at approximately latitudes ðŸ¶ðŸ¶70ðŸ¶8.69ðŸ¶ËˆE and longitudes ðŸ¶90 34Ëˆ224ËˆËˆN and interrogated using Proton induced X-ray emission (PIXE) technique for their elemental content. PIXE was chosen because of its sample nondestructive and it does not contaminate the environment. The result obtained varied between 24.3 â€“ 632303.3 ppm. The world Health Organization recommends that sites with Pb concentration above 400 ppm are inimical to human health and ordered that children be evacuated from such areas. Exposure to Pb poisoning may cause anemia, weakness, and Kidney and brain damage; particularly in children.